Utilizing Google Trends for the Identification of Evergreen Topics in Online Media Akurat.co - Adzhari, Noor Latifah; Priatna, Wahyu Budi (Indonesian Scientific Publication, 2025)
The development of digital technology has changed how news is produced and consumed, requiring online media to adopt strategies that allow articles to remain relevant over time. Previous studies using Google Trends have focused on specific practical applications, such as analyzing newsroom patterns in Madania.co.id, assessing the impact of COVID-19 on the stock market, improving product keyword competitiveness, forecasting airport passenger arrivals, identifying public health risks, and analyzing social media usage trends. However, none of these studies investigate how Google Trends is used within editorial decision-making to support sustainable evergreen content production. This study fills that gap by examining how editors at Akurat.co utilize Google Trends to identify and select evergreen topics that continue attracting readers in the long term. The research uses a qualitative method through observation, interviews, and literature study conducted during an internship at PT Akurat Sentra Media. This internshipbased approach enables direct access to editorial routines, allowing deeper understanding of how data analytics supports decision-making in the newsroom. The findings reveal that Google Trends helps editors recognize topics with stable search interest such as education, lifestyle, and health thus supporting a more focused and data-driven SEO strategy. This study contributes to the discussion on data-driven journalism by demonstrating how search analytics can guide editorial sustainability practices in Indonesian online media. The implication is that integrating search data into newsroom workflows can improve content quality, match reader needs, and enhance the long-term competitiveness of digital news platforms.